2020
DOI: 10.1101/gad.333369.119
|View full text |Cite
|
Sign up to set email alerts
|

The rRNA m6A methyltransferase METTL5 is involved in pluripotency and developmental programs

Abstract: Covalent chemical modifications of cellular RNAs directly impact all biological processes. However, our mechanistic understanding of the enzymes catalyzing these modifications, their substrates and biological functions, remains vague. Amongst RNA modifications N 6-methyladenosine (m 6 A) is widespread and found in messenger (mRNA), ribosomal (rRNA), and noncoding RNAs. Here, we undertook a systematic screen to uncover new RNA methyltransferases. We demonstrate that the methyltransferase-like 5 (METTL5) protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
119
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(129 citation statements)
references
References 60 publications
9
119
1
Order By: Relevance
“…is also an American Cancer Society Research Professor; 3. During the preparation of this manuscript for publication, two other studies have been published that also documented the role of METTL5 as an 18S rRNA-specific methyltransferase (57,58). And in one of the studies METTL5 has also been shown to regulate stress-related genes in C. elegans (58), which suggests the involvement of METTL5 in stress response may be conserved during evolution.…”
Section: Tcga Data Analysismentioning
confidence: 89%
“…is also an American Cancer Society Research Professor; 3. During the preparation of this manuscript for publication, two other studies have been published that also documented the role of METTL5 as an 18S rRNA-specific methyltransferase (57,58). And in one of the studies METTL5 has also been shown to regulate stress-related genes in C. elegans (58), which suggests the involvement of METTL5 in stress response may be conserved during evolution.…”
Section: Tcga Data Analysismentioning
confidence: 89%
“…METTL5 was defined as the methyltransferase of 18S rRNA, ZCCHC4 was defined as the methyltransferase of 28S rRNA, and TRMT112 acts as a methyltransferase activator to stabilize METTL5 in cells 37 . METTL5 was also reported to be involved in the pluripotency and differentiation potential of mouse embryonic stem cells and the fly behavior of Drosophila 38,39 .…”
Section: Methyltransferases/writersmentioning
confidence: 99%
“…Note-added-in-proof: While this manuscript was under review, multiple studies showed that METTL5 mediates m6A methylation on the small subunit ribosomal RNA in flies, worms, mice, and human cells [13][14][15][16] . Collectively, our findings as well as the above referenced recent studies further support the conclusion that METTL5 is an evolutionarily conserved rRNA m6A methyltransferase.…”
Section: Analysis Of M6a Rna Methylation In Caenorhabditis Elegansmentioning
confidence: 99%